Combined environmental risk assessment for the antiviral pharmaceuticals ganciclovir and valganciclovir in Europe. (6th March 2017) - Straub, Jürg Oliver
Abstract: Potential environmental risks of the old antiviral pharmaceuticals ganciclovir (GCV) and valganciclovir (VGCV) were reassessed based on new environmental fate and chronic ecotoxicity tests and on actual use data for Europe. Valganciclovir is hydrolyzed to GCV by intestinal and hepatic esterases, and hence the new environmental tests only refer to GCV. A sorption study showed that GCV will not sorb significantly, excluding the soil as a relevant environmental compartment. Despite earlier data suggesting nondegradability, a new water/sediment fate test showed GCV to be primarily and ultimately degraded and to be nonpersistent. The chronic ecotoxicity tests with algae and daphnids resulted in no inhibition at the highest tested concentrations, whereas a fish partial life cycle test, selected in view of mammalian mutagenicity and reprotoxicity data, showed effects on growth of the young fish, but not on gametogenesis, fertilization, embryogenesis, or teratogenicity. Predicted environmental concentrations were derived based on actual per capita use data for European countries for 2004 to 2014, and the highest was selected for the risk assessment. A comparison of predicted environmental concentrations with predicted no‐effect concentrations shows no significant risk for wastewater treatment, surface waters, groundwater, or sediment. In addition, potential risks to (semi)aquatic top predators or to human consumers of water and fish are exceedingly low. Environ Toxicol Chem 2017;36:2205–2216. © 2017 The Author. Environmental Toxicology and Chemistry Published by Wiley Periodicals, Inc. on behalf of SETAC